Equal area of stepped waveform generation technique for multilevel inverter - Tohtayong, Majdee
This research work proposes a stepped waveform generation technique named equal area stepped waveform (EASW) for the multilevel inverter, as an alternative to optimized harmonic stepped waveform (OHSW). In the OHSW technique, nonlinear equations are solved numerically for computing the firing angle of the power switches in the multilevel inverter. In the EASW approach, the intended stepped waveform is generated by finding how a given quarter cycle sinusoidal can be best approximated to a stepped waveform such that the area under the curve in both cases are identical. Once decided on identical area locations, the estimated angles are calculated. The effects of calculated angles on the total harmonic distortion (THD) by both techniques are compared for preferential utility through experimental results by testing on the prototype of a multilevel inverter in firing the switches of the similar circuits for 7- and 9-level stepped waveform generation at the modulation index 0.85. The proposed EASW technique shows THD=16.3 %, and 10.9 % as compared to THD= 18.5 %, and 11.8 % by OHSW technique for the multilevel inverter. Likewise, the EASW technique is implemented to 7-, 9-, 11-, 13-, and 15-level stepped waveforms at the modulation index 1.00, which provided improved results on waveform shapes and THD. Ultimately, the lowest THD of this research work is 4.2 %, which is revealed on 15-level stepped waveforms.